2018
DOI: 10.1051/shsconf/20184200034
|View full text |Cite
|
Sign up to set email alerts
|

Teachers’ Beliefs and Perceptions of Code Switching in English as Foreign Language Classroom

Abstract: Abstract. In Indonesia, the use of only English as a medium of instruction in English as a Foreign Language (EFL) classroom is highly demanded. The present study investigates how code-switching is perceived by High School teachers in Kupang city, East Nusa Tenggara province, Indonesia, in teaching English. Specifically, it aims to find out the teachers' beliefs and perceptions towards the use of Indonesian language (L1) as their pedagogical instrument in teaching English in EFL classrooms. To achieve that goal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…The findings showed that the classroom participants hold positive attitudes toward teacher's CS. Many other studies, locally and internationally, revealed the same positive perceptions of teacher's CS in the classroom (e.g., Ibrahim et al, 2013;Leoanak & Amalo, 2018;Suteja & Purwanti, 2017). Al-Nofaie (2010), for instance, found that the teachers and students had positive attitudes toward the use of L1 for certain functions and reasons.…”
Section: Teachers and Students' Attitudes To Csmentioning
confidence: 72%
See 1 more Smart Citation
“…The findings showed that the classroom participants hold positive attitudes toward teacher's CS. Many other studies, locally and internationally, revealed the same positive perceptions of teacher's CS in the classroom (e.g., Ibrahim et al, 2013;Leoanak & Amalo, 2018;Suteja & Purwanti, 2017). Al-Nofaie (2010), for instance, found that the teachers and students had positive attitudes toward the use of L1 for certain functions and reasons.…”
Section: Teachers and Students' Attitudes To Csmentioning
confidence: 72%
“…A lot of research has been conducted in different contexts to measure the classroom participants' perceptions on CS (Al-Nofaie, 2010;Alrabah et al, 2016;Bilgin, 2016;Ibrahim, Shah, & Armia, 2013;Leoanak & Amalo, 2018;Suteja & Purwanti, 2017). The overall findings revealed that both teachers and students hold positive attitudes toward using L1 to support L2 teaching and learning process, although Cheng (2013) observed that teachers go to classes with a negative attitude toward CS; despite this, its usage is still prevalent in the class.…”
Section: Teachers and Students' Perceptions Of Classroom Csmentioning
confidence: 99%
“…Results in the research of Leoanak and Amalo (2018) show that they disagree with the strict separation of Bahasa Indonesia and English as they are part of the sociolinguistic arrangement of Indonesian society. At the same time, Indonesians put high regard to these languages.…”
Section: Karena Agar Lebih Mengasah Kemampuan Bahasa Inggris Dan Lebi...mentioning
confidence: 89%
“…Sadly, English classes in Indonesia are taught in the local language, so there are no models recognizable for such issues. The Indonesian English teachers, according to Leoanak and Amalo (2018), even strongly agree that if they use English in their classes, the better the students' assessment results. With more than 80% in both groups of pre-service teachers prefer teaching in both English and the local language.…”
Section: Perceptions On Code-switchingmentioning
confidence: 99%
See 1 more Smart Citation